Взаимозависимость особенностей цирконов и деформационных показателей пород Орехово-Павлоградской межблоковой зоны - Осьмачко, Л.С.; Демедюк, В.В. (Мінералогічний журнал, 2010)
Для участка Орехово-Павлоградской межблоковой зоны количество и разнообразие генераций петроструктурных элементов сопоставимо с количеством и разнообразием генераций цирконов. Что может быть следствием формирования этих образований благодаря одним и тем же геологическим причинам — неоднократным деформационным преобразованиям. Для ділянки Оріхово-Павлоградської міжблокової зони кількість та розмаїття генерацій петроструктурних елементів зіставима з кількістю та розмаїттям генерацій цирконів. Це може бути результатом формування зазначених утворень внаслідок одних і тих самих геологічних явищ — неодноразових деформаційних перетворень. Geological bodies of Orekhovo-Pavlograd interblock zone (OPIZ) being diverse as to their substance filling were formed by dynamometamorphic paragenesises quite close as to their parameters. The components of such parageneses (micro- and mesostructure forms) differ in PT conditions of formation, material filling, orientation of linear elements ... About five generation of such structural forms have been distinguished. They are classified as residual neoforms — formed after deformation. That is, all petrographic varieties of the suture zone have undergone quite close structural evolution: four to five stages of dislocation rock transformations in time and space of directions of main functional strains and PT conditions. The surveyed rock-bodies enclose the same four-five varieties of zircons in which temporary anchors 3.6; 3.4—3.3; 2.8—2.7; 2.0 Ga are known. With all this, the main planes of all the studied structures are oriented submeridionally. This monoclinal orientation of different-age petro-structural elements is possible only under the most intensive sheared deformation (which has initiated the plastic state of geological environment) at the time of one of the last stages of transformation. Therefore, the primary ratios (of above-below and before-later) rock varieties and OPIZ cannot be recovered. Proceeding from the system of geological objects and processes which have been formed, the structure of both survey station and OPIZ as a whole corresponds to shear-scaly, or blend submeridional strike and subvertical fall zone. The comparability of the number of varieties of zircons and temporary anchors, structural elements and stages of rocks’ transformation of OPIZ, demonstrates the genetic unity of the processes of substance-structural transformations both at the level of rocks, rock-forming minerals and accessories. That is temporary anchors also display the moments of formation of zircons and reliсt linearity (3.6 Ga), banding –1 and –2 (3.4—3.3; 2.8—2.7 Ga) due to the appearance of granitoid material, and most powerful performance of lenticularity (2.0, 1.7? Ga) with forming the mineral linearity in two directions. The lenticularity-blending concentrated as to the area and intensity, accompanied by secondary crystallization phenomena at the time of the latest of the designated phases has determined the final laminar structure of OPIZ.